Differences In Platelet and Thrombin Levels In Preeclampsia and Normal Pregnancy - Gistin Husnul; Joserizal Serudji; Vaulinne Basyir (Syntax Corporation, 2022)
Background; Preeclampsia is a pregnancy-specific syndrome that can affect any organ system. The incidence of preeclampsia and eclampsia is different for each country. Changes in endothelial function are considered to be the main cause of symptoms of preeclampsia such as hypertension, proteinuria, and activation of the hemostatic system. Changes in endothelial function that occur in preeclampsia will lead to increased coagulation, fibrin deposition in the microvasculature which results in disruption of placental perfusion. Platelets and thrombin are part of the coagulant factors. Extensive endothelial injury in severe preeclampsia causes a large use of platelets resulting in a decrease in the number of platelets. Thrombin is a serine protease that plays an important role in the coagulation cascade, thrombosis, and hemostasis. Coagulation markers such as platelets and thrombin will affect the coagulation cascade so that they can be used as markers of the progression of preeclampsia. Therefore, it is important to know the extent to which coagulation markers such as platelets and thrombin have an effect in patients with preeclampsia and normal pregnancy. This study to determine the difference in levels of platelet and thrombin in preeclampsia and normal pregnancy Methods: This study is observational with a cross-sectional comparative study design. Sampling was conducted from March 2020 to March 2021. A total of 66 patients were investigated, with 33 samples of preeclampsia and 33 samples of normal pregnancy. The independent sample T-test was used for statistical analysis. Results: The mean levels of Platelet in the preeclampsia group were lower at 214030.3 ± 111128.44 /mm3 while normal pregnancy was 274151.52 ± 88857.02/mm3. The results of statistical tests showed that there was a significant difference in levels of Platelet between the preeclampsia and normal pregnancy groups (p <0,05). The mean thrombin level in the preeclampsia group was higher at 72.23 ± 7.99 ng/mL, while in normal pregnancy it was 63.70 ± 8.92 ng/mL. The difference in thrombin levels between the preeclampsia and normal pregnancy groups was statistically significant (p<0.05) Conclusion: Preeclampsia was associated with Lower levels of Platelet and higher level of thrombin than normal pregnancy. There was a significant difference in the mean levels of Platelet and thrombin between preeclampsia and normal pregnancy.